Electric‐field penetration depth and dielectric spectroscopy observations of human skin. Issue 2 (25th September 2019) - Maruyama, Yuko; Kamata, Hayato; Watanabe, Seiei; Kita, Rio; Shinyashiki, Naoki; Yagihara, Shin
Abstract: Background: The dynamic behavior of water molecules remains an important subject for understanding human skin. The change in the dynamics of water molecules from those in bulk water can be effectively observed by dielectric spectroscopy. To study water in the human skin in vivo, non‐invasive and non‐destructive measurements are essential. Since many unknowns remain from previous research, in this report we employ a two‐layer dielectric model to evaluate the penetration depth of the electric field and use the results in measurements on human skin. Materials and Methods: We used open‐ended coaxial probes with different diameters to perform time‐domain reflectometry (TDR) measurements for an acetone‐Teflon double‐layer model and for human skin from various parts of the body. Results: The electric‐field penetration depth obtained from model measurements increases with the increasing outer diameter of open‐ended coaxial electrodes. For skin measurements, the relaxation strength corresponding to the water content shows a clear dependence on the epidermal thickness of the measured body parts. Conclusion: We determined the depth distribution of the water content of skin from results of dielectric measurements obtained using electrodes with various electric‐field penetration depths. We found exponential decays with the thickness of the epidermis of each body part for several examinees. This study suggests an effective method for detailed evaluations of human skin.